FORENSIC ENTOMOTOXICOLOGICAL EVALUATION OF CARRION INSECTS FOUND ON PIGS EUTHANIZED WITH SNIPER INSECTICIDE DICHLORVOS IN IBADAN - Tyokumbur, Emmanuel Teryila; Ilori, Catherine (FUDMA JOURNAL OF SCIENCES, 2025)
Dichlorvos is a commonly used suicide agent in Nigeria that needs to be forensically evaluated. A forensic entomotoxicological evaluation of carrion insects found on pigs euthanized with sniper insecticide was carried out at the far backend of the University of Ibadan. Two domestic pigs, Sus scrofa weighing 5.2kg and 10kg were used as surrogate human models for the study. One of the pigs was euthanized with 0.157ml/kg of sniper insecticide while the other was sacrificed without poison and used as the control experiment. Arthropods were collected from the decomposing carrions using a sweep net and were preserved in 70% ethanol for identification. Larvae and pupae were also collected and preserved in 70% ethanol. The families of arthropods namely; Calliphoridae, Muscidae and Dermestidae were found, while five species namely; Chrysomya albiceps, Chrysomya megacephala, Lucilia sericata, Dermestes maculatus and Musca domestica were found. The succession pattern and abundance of the carrion insects, effects of poison and environmental variables such as temperature and humidity on them were studied. The family Calliphoridae were the most abundant and the first to colonize the decomposing carrion. The Calliphoridae had 103 individuals followed by the Muscidae with 17 individuals and the Dermestidae with 4 individuals. It was observed from this study that carrion insects are very important in the decomposition of pig carcass. It was also observed that these insects are of forensic importance and can be used in forensic investigations since pigs are biologically similar to humans, this can be linked to solving human crime cases
Keywords: Entomotoxicology; Sniper insecticide; Pigs; Decomposition; Carrion insects